Implementation of Differentiated Learning to Enhance Elementary School Students' Mathematical Critical and Creative Thinking Skills - Lestari, Fuji; Alim, Jesi Alexander; Noviyanti, Mery (Universitas Pendidikan Ganesha, 2024)
The critical and creative thinking abilities of students are still low, with the greatest potential for development lying in mathematics education. This research aims to analyze the effectiveness of implementing differentiated instruction to enhance students' critical and creative thinking abilities. The study employs a quantitative design with a quasi-experimental two-group model, comprising an experimental group and a control group. The research participants consisted of 21 students in the experimental group and 21 students in the control group. Data collection instruments used were tests of critical and creative thinking. Data analysis techniques involved statistical tests, including tests for normality, homogeneity, and hypothesis testing on pre-test and post-test results. The outcomes of the N-Gain Score calculations indicate that the average N-Gain Score for critical thinking abilities in the experimental group is 61.1%, which falls into the category of moderately effective. On the other hand, the control group only reaches 29.7%, which falls into the category of ineffective. For creative thinking abilities, the average N-Gain Score in the experimental group is 59.2%, also falling into the moderately effective category, while the control group only achieves 45.3%, falling into the less effective category. Additionally, the results of student grouping based on learning abilities reveal that the post-test scores of critical and creative thinking abilities for students in the upper group are higher compared to students in the middle and lower groups within the experimental group.